A máquina apocalíptica e o tempo do fim: a experiência do mal e a política como tragédia em Dostoiévski - Prada, Thiago da Silva (2023)
This study proposes an inquiry into the literary work of the Russian author Fiódor Dostoiévski in an interpretation of his literature as a dramatic reactualization of the krisis, to draw up the concept of an “apocalyptic machine” and extract some elements to think the politics as a tragedy from the experience of the evil. We start with the assumption that his literary work is a theodicy, an attempt to understand and accept the existence of the evil in a world created by a perfect, fair, and loving God, who sent Christ to save the whole of mankind and serve as an absolute moral ideal, as opposed to an diabolodicy, the judgment upon the divine creation for the existence of the evil and the search for the justice through the world correctness. From the problem of the evil (the origin and meaning of human suffering), and from the politics as tragedy and as an everlasting tension field, our objective was to present a new interpretation of Dostoiévski’s literary work, as well as the production of a new concept of “apocalyptic machine”, and think his writings under the political perspective of the tragedy, by analyzing the seeking for the best social order, as from the establishment of an earhly paradise, in its religious and secularized version. Our task was to examine, the evil experience, the death, the suffering, and the tragedy, based on the antinomy of two antagonistic and irreconcilable views of the world. From this ground, we have established two main theoretical foundations, the politicaltheological philosophy of Giorgio Agamben and the essayistic philosophy of Albert Camus, along with a series of authors to think over the matter of evil, analysis of Dostoiévski’s writings and themes of the politics. Thus, our research has a multidisciplinary character by articulating philosophy, politics, and art, more particularly literature, together with other areas of knowledge to comprehend the complexity of Dostoiévski’s literary work. We have selected two main books: The Idiot and The Brothers Karamazov, to evaluate the internal content of their characters, scenes, and dialogues, relating and opposing them to the nihilistic and Christian vision present in his works, taking them to their ultimate consequences and taking out from them the elements to elaborate the concept of “apocalyptc machine” together with the time of the end, thinking over Dostoiévski’s writings in the tragic perspective of the politics in which both positions aim at the foundation of the best social order, but consequently have more suffering and never reconcile with each other